GAMBARAN DISABILITAS AKIBAT MIGREN PADA REMAJA DENGAN MENGGUNAKAN P edMIDAS - Acep Ivan Saputra,* Yusuf Wibisono,* Ahmad Rizal Ganiem* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION MIGRAINE IS A PRIMARY HEADACHE THAT IS OFTEN FOUND IN CHILDREN AND ADOLESCENT MIGRAINE IS ALSO THE MOST FREQUENT CAUSE OF LOW ATTENDANCE IN SCHOOL PEDIATRIC MIGRAINE DISABILITY ASSESSMENT PEDMIDAS IS A SENSITIVE RELIABLE AND VALID ASSESSMENT TOOL FOR CHILDREN AND ADOLESCENT